Transnasal Esophagoscopy Examination in Outpatient Unit, Department of Otorhinolaryngology Head and Neck Surgery, Dr. Soetomo Hospital, Surabaya - Perdana, Rizka Fathoni (Folia Medica Indonesiana, 2020)
Esophagoscopy is the standard examination standard for evaluation, diagnosis, screening and surveillance of esophageal diseases. Although it is often done, esophagoscopy costs a lot, is inconvenient, and risks complications, including cardiopulmonary complications because patients usually require routine sedation in the implementation of conventional esophagoscopic procedures. The purpose of this study is to get an overview of the results of the implementation of transnasal esophagoscopy in Department of Otorhinolaryngology Head and Neck Surgery, Division of Broncho-oesophagology, Dr. Soetomo Hospital, Surabaya, between 1 September 2012 and 30 April 2015. This study was a retrospective descriptive study with a population of all patients undergoing esophagoscopic examinations during this period. Data is taken from medical records of new patients undergoing transnasal esophagoscopy. Inclusion criteria were all patients who had been tested for transnasal esophagoscopy, and exclusion criteria were incomplete medical record data. There were 35 patients who underwent transnasal esophagoscopy examination at Department of Otorhinolaryngology Head and Neck Surgery, Division of Broncho-oesophagology, Dr. Soetomo Hospital, Surabayaduring the study period. The mean of patients who participated in the study was 54.17 ± 14.02. 23 male patients (63.89%), while 12 female patients or 34.11%. Indications of dysfagi are found in all age groups, most in the age group 51-70 years. Metastases in head and neck malignancies are found in the age group 31 - 50 years and 51 - 70 years. Indications for heartburn are found in the age group 21-50 years and 51-70 years. In conclusion, the results of transnasal esophagoscopic examination showed that most patients had a normal picture (60%) and a positive picture with an esophageal abnormality of 40%. The most common features are lesions in the mucosal esophagus lumen, scar, masses and stenosis.